Thermally activated exchange narrowing of the Gd3+ ESR fine structure in a single crystal of Ce1-xGdxFe4P12 (x approximate to 0.001) skutterudite - Garcia, F. A.; Venegas, Pablo Antonio [UNESP]; Pagliuso, P. G.; Rettori, C.; Fisk, Z.; Schlottmann, P.; Oseroff, S. B. (Amer Physical Soc, 2011)
We report electron spin resonance (ESR) measurements in the Gd3+ doped semiconducting filled skutterudite compound Ce1-xGdxFe4P12 (x approximate to 0.001). As the temperature T varies from T similar or equal to 150 K to T similar or equal to 165 K, the Gd3+ ESR fine and hyperfine structures coalesce into a broad inhomogeneous single resonance. At T similar or equal to 200 K the line narrows and as T increases further, the resonance becomes homogeneous with a thermal broadening of 1.1(2) Oe/K. These results suggest that the origin of these features may be associated with a subtle interdependence of thermally activated mechanisms that combine: (i) an increase with T of the density of activated conduction carriers across the T-dependent semiconducting pseudogap; (ii) the Gd3+ Korringa relaxation process due to an exchange interaction J(fd)S.s between the Gd3+ localized magnetic moments and the thermally activated conduction carriers; and (iii) a relatively weak confining potential of the rare earth ions inside the oversized (Fe2P3)(4) cage, which allows the rare earths to become rattler Einstein oscillators above T approximate to 148 K. We argue that the rattling of the Gd3+ ions, via a motional narrowing mechanism, also contributes to the coalescence of the ESR fine and hyperfine structure.